2020
DOI: 10.1002/mgg3.1292
|View full text |Cite
|
Sign up to set email alerts
|

The first concurrent detection of mitochondrial DNA m.3243A>G mutation, deletion, and depletion in a family with mitochondrial diabetes

Abstract: BackgroundMitochondrial diabetes (MD) is a rare monogenic form of diabetes and divided into type l and type 2. It is characterized by a strong familial clustering of diabetes with the presence of maternal transmission in conjunction with bilateral hearing impairment in most of the carriers. The most common form of MD is associated with the m.3243A>G mutation in the mitochondrial MT‐TL1, but there are also association with a range of other point mutations, deletion, and depletion in mtDNA.MethodsThe mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Most patients have normal or lean body mass, with an average BMI of less than 20 kg/m 2 4 . Most patients have negative results for islet autoantibodies 5 . Abnormalities in glucose metabolism associated with multiorgan damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most patients have normal or lean body mass, with an average BMI of less than 20 kg/m 2 4 . Most patients have negative results for islet autoantibodies 5 . Abnormalities in glucose metabolism associated with multiorgan damage.…”
Section: Discussionmentioning
confidence: 99%
“…4 Most patients have negative results for islet autoantibodies. 5 Abnormalities in glucose metabolism associated with multiorgan damage. Special attention should be paid to patients with early-onset diabetic retinopathy.…”
Section: Idegasp +Carbosementioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] In particular, the well-known m.A3243G mutation in tRNA Leu(UUR) was implicated in the pathogenesis and progression of T2DM in many families worldwide. [9][10][11] This mutation affected the structural stability, aminoacylation rate and post-transcriptional modification of tRNA Leu(UUR) . 12 In addition to the m.A3243G mutation, some case-control studies suggested that tRNA Trp A5514G and tRNA Ser(AGY) C12337T, 13 tRNA Glu A14692G, 14 tRNA Ala T5587C and ND5 T12338C 15 mutations were associated with T2DM.…”
Section: Introductionmentioning
confidence: 99%